Pengembangan Bahan Ajar “Eksplorasi Metamorfosis” berbasis Problem Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Fase B Sekolah Dasar - Dzakiroh, Adilla; Eki Saputri, Aprilia; Muyassaroh, Izzah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low problem-solving skills of third-grade elementary students in understanding animal metamorphosis. The absence of contextual teaching materials causes students to struggle in solving problems and participating actively in learning. This study aims to develop a teaching material called “Eksplorasi Metamorfosis” based on the Problem Based Learning (PBL) model to improve students' problem-solving abilities. The research method used was Design and Development (D&D), with the ADDIE model (analysis, design, development, implementation, and evaluation). Data collection techniques included questionnaires and tests involving 25 third-grade as subjects. Data were analyzed using qualitative and quantitative methods with a Likert scale. The developed teaching material follows the PBL syntax in a structured sequence, incorporates problem solving indicators, and aligns with specific learning objectives. The material offers strengths in its deeper exploration of metamorphosis content, a focused assessment approach that has not been widely developed, and its contextual presentation through an interactive design that encourages active student involvement. Expert validation results showed an overall score of 96.44%, categorized as very feasible. Cognitive test results showed an N-Gain score of 0.72, indicating high improvement in students' problem-solving abilities. Meanwhile, skill and affective assessments produced results ranging from good to excellent, reflecting students’ progress in both competence and positive attitudes during the learning process. It can be concluded that the “Eksplorasi Metamorfosis” teaching material is highly feasible to implement in learning and effective in improving problem-solving skills in the topic of metamorphosis for Phase B elementary students.